2016
DOI: 10.17656/sjes.10033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impactor Design on Unidirectional and Woven fiber Reinforced Composites

Abstract: Since impact damage resistance is such an important property for composite materials, this research is devoted to study the effect of impactor design on the impact properties of epoxy composites reinforced with unidirectional glass, unidirectional carbon, woven glass and hybrid woven (glass + carbon) fibers . This research shows changing the impactor design have no effect on impact properties of woven reinforced composites while it has a significant effect on unidirectional fiber reinforced composites, impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These failure mechanisms contribute to the amount of energy absorbed by the FML system, in which it is clearly can be seen that the woven fibre absorb more energy compared to unidirectional fibre during static indentation loading. Ahmed et al [14] also reported that the woven type of fibre resulted in minimum deformation and maximum force and energy. He concluded that woven type composites have good ability to absorb large energy, while unidirectional type of fibre showed low energy absorption [14].…”
Section: Quasi-static Indentation Test (Qsi)mentioning
confidence: 98%
See 1 more Smart Citation
“…These failure mechanisms contribute to the amount of energy absorbed by the FML system, in which it is clearly can be seen that the woven fibre absorb more energy compared to unidirectional fibre during static indentation loading. Ahmed et al [14] also reported that the woven type of fibre resulted in minimum deformation and maximum force and energy. He concluded that woven type composites have good ability to absorb large energy, while unidirectional type of fibre showed low energy absorption [14].…”
Section: Quasi-static Indentation Test (Qsi)mentioning
confidence: 98%
“…Ahmed et al [14] also reported that the woven type of fibre resulted in minimum deformation and maximum force and energy. He concluded that woven type composites have good ability to absorb large energy, while unidirectional type of fibre showed low energy absorption [14].…”
Section: Quasi-static Indentation Test (Qsi)mentioning
confidence: 98%
“…The results revealed that 0.2 Wt.% of MWCNTs improve tensile properties, whereas 0.6 Wt.% of MWCNTs improve impact characteristics (Fadhil et al, 2016). Ahmed (2016) used different designs of the impactor in drop-weight impact test (bullet, cone and hemispherical) and investigated this effect on the impact properties of epoxy composites reinforced with unidirectional glass, unidirectional carbon, woven glass and hybrid woven (glass þ carbon) fibers. Results showed that changing the impactor design had no effect on the impact characteristics of composites reinforced with woven fiber, whereas it has a huge effect on unidirectional fiber-reinforced composites.…”
Section: Mmms 166mentioning
confidence: 99%
“…Results showed that changing the impactor design had no effect on the impact characteristics of composites reinforced with woven fiber, whereas it has a huge effect on unidirectional fiber-reinforced composites. Indentation and perforation were observed as impact damage behavior of woven composites while matrix cracking and splitting along the fiber direction and the fracture were for unidirectional fiber-reinforced composites (Ahmed, 2016). Others studied hybrid armor made of UHMWPE and soft structure panel to increase energy absorption (Liu et al, 2018).…”
Section: Mmms 166mentioning
confidence: 99%
“…Payman S. A. [9] studied the effect of impactor design on the impact properties of epoxy composites reinforced with unidirectional glass, unidirectional carbon, woven glass and hybrid woven (glass + carbon) fibers. This research shows that changing the impactor design have no effect on impact properties of woven reinforced composites while it has a significant effect on unidirectional fiber reinforced composites, and glass fiber reinforced composites have a better impact property than carbon reinforced composites.…”
Section: Introductionmentioning
confidence: 99%